Coordination level, spatio-temporal effects and driving mechanisms of Chinese agricultural water–land–economy composite system from the perspective of sustainable development - Shanwei Li; Yongchang Wu; Guangxuan Dai; Xueyuan Chen; Meng Li (Scientific Reports)
Abstract Investigating the coupling mechanism of the agricultural “Water-Land-Economy” composite system(CS) and proposing optimization measures are crucial for advancing agricultural sustainable development in China. This study draws upon data spanning 2000 to 2020 from all 31 provinces of China. It examines the development trends, spatiotemporal characteristics, and driving mechanisms of coordinated development using various analytical techniques. The findings reveal that: (1) Regarding coordination level, the CS coordination level is on the rise, accompanied by distinct dynamic evolution patterns among regions and provinces. (2) Regarding spatial effects, the coupling coordination displays a clustered distribution pattern, with the eastern region acting as the core cluster, and a diminishing radiation capacity from east to western with decreasing geographical proximity. (3) Regarding driving mechanisms, the spatial differentiation in coupling coordination is attributed to the collective influence of various factors, with irrigation coverage and land-water coordination degree emerging as primary drivers. Building upon these insights, recommendations spanning policy adjustment, technological support, regional governance, and economic guarantee are proposed to foster the harmonized development of agricultural resources, environment, and economy, thus realizing the objective of sustainable agricultural progression.